An acoustic gap between the NICU and womb: a potential risk for compromised neuroplasticity of the auditory system in preterm infants - Lahav, Amir; Skoe, Erika (Frontiers in Neuroscience, 2014)
The intrauterine environment allows the fetus to begin hearing with low frequency sounds in a protected fashion, ensuring optimal development of the peripheral and central auditory system. However, the auditory nursery provided by the womb vanishes once the preterm newborn enters the high-frequency (HF) noisy environment of the neonatal intensive care unit (NICU). The present article draws a concerning line between auditory system development and HF noise in the NICU, which is not necessarily conducive to fostering this development. Overexposure to HF noise during critical periods disrupts the functional organization of auditory cortical circuits. As a result, we theorize, the ability to tune out noise and extract acoustic information in a noisy environment may be impaired, leading to a variety of auditory, language, and attention disorders. Additionally, HF noise in the NICU often masks human speech sounds potentially important to the preterm infant, whose exposure to linguistic stimuli is already restricted. Understanding the impact of the sound environment on the developing auditory system is an important first step in meeting the developmental demands of preterm newborns undergoing intensive care.